Electrospun PVA/α‐mangostin nanofibers, their anti‐bacterial ability and anti‐oxidation performances. Issue 6 (23rd September 2022) - Dung, Hoang Tran; Van Huy, Nguyen; Dung, Ngo Thanh; Tung, Doan Thanh; Yen, Nguyen Thi; Thanh, Ngo Ba; Hien, Nguyen Thi; Hoang, Thai; Lu, Le Trong; Chinh, Nguyen Thuy
Abstract: α‐mangostin which has been extracted from mangosteen peel is known as an excellent bioactive substance with high anti‐oxidation, anti‐bacterial, anti‐inflammatory, etc. The application of α‐mangostin in the biomedicine field is potential and promising. However, the α‐mangostin has a poorly solubility in aqueous. Using polymers as carriers to improve the solubility of α‐mangostin has been attracted in research. In this work, poly(vinyl alcohol) (PVA) crosslinked with citric acid has been used as a carrier to enhance the solubility of α‐mangostin. The PVA/α‐mangostin nanofibers were prepared by electrospinning method with the ratio of PVA/α‐mangostin varied 100/0, 100/1 and 100/3 (w/w). The obtained PVA/α‐mangostin nanofibers have smooth and homogenous surface. The introduction of α‐mangostin into PVA can increase mechanical properties of PVA. The slight shift in wavenumbers characterized for stretching vibration of hydroxyl groups in the PVA/α‐mangostin nanofibers as compared to PVA nanofibers suggested that hydroxyl groups in PVA can interact with hydroxyl groups in α‐mangostin. The solubility of α‐mangostin in ethanol/pH buffer solutions was enhanced significantly in the presence of PVA. The antibacterial and anti‐oxidation ability of PVA/α‐mangostin nanofibers was increased as increasing α‐mangostin concentration. These results showed that the nanofibers are potential for application in biomedicine field as a wound dressing material or in food industry. Abstract :